2012
DOI: 10.1029/2011ja017398
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of dayside equatorial ionospheric electric fields and electrojet currents produced by magnetospheric substorms during sawtooth events

Abstract: .[1] Substorms cause significant disturbances in the ionosphere. However, it has not been well understood how the electric field and electrojet in the dayside equatorial ionosphere respond to substorm onset. Previous studies found that the equatorial electric field, after substorm onset, could be eastward or westward. Because the onset of isolated substorms is often related to a northward turning of the interplanetary magnetic field (IMF), the measured total electric field is determined by contributions from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 49 publications
5
49
0
Order By: Relevance
“…Second, during this period of time the sub-storm activity was less intensive than during the initial phase of the storm, which could play a role on the efficiency of the PPEF. It is known that substorms can enhance the PPEF or can serve themselves as a source of PPEF (Huang 2012). Finally, the longitudinal The second positive storm on the nightside correlates well with a new increase of the counter electrojet, especially in data of SWA and SWC (rows VIII and IX), i.e., in the same manner as during the first sub-event.…”
Section: Resultsmentioning
confidence: 66%
“…Second, during this period of time the sub-storm activity was less intensive than during the initial phase of the storm, which could play a role on the efficiency of the PPEF. It is known that substorms can enhance the PPEF or can serve themselves as a source of PPEF (Huang 2012). Finally, the longitudinal The second positive storm on the nightside correlates well with a new increase of the counter electrojet, especially in data of SWA and SWC (rows VIII and IX), i.e., in the same manner as during the first sub-event.…”
Section: Resultsmentioning
confidence: 66%
“…Generally, the equatorial electric field perturbation after substorm onset could be either eastward or westward. Huang [] showed that the westward electric field perturbation is in many cases related to a northward turning of the interplanetary magnetic field (IMF), which often coincides with substorm onset. Huang [] also showed that the equatorial electric field perturbation after substorm onset is eastward when the IMF is continuously southward around the onset without a northward turning of the IMF.…”
Section: Resultsmentioning
confidence: 99%
“…Later, the onset of a substorm around 1725 UT caused another PPEF and resulted in rapid enhancement in the zonal electric field over Brazil which is termed as PPEF‐2 phase. The penetration of substorm‐induced electric fields from high latitudes to low latitudes is reported by several studies during other storm events [ Gonzales et al ., ; Kikuchi et al ., ; Sastri et al ., ; Huang , ]. It has been reported earlier that the zonal electric field disturbance is eastward during daytime at the low latitudes with the positive geomagnetic field disturbance under southward IMF Bz during the storm time substorm [ Huang et al ., and Huang , , ].…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported earlier that the zonal electric field disturbance is eastward during daytime at the low latitudes with the positive geomagnetic field disturbance under southward IMF Bz during the storm time substorm [ Huang et al ., and Huang , , ]. Huang [, ] reported that the increased convection at substorm onset causes an enhanced magnetosphere electric field which penetrates into the dayside low‐latitude ionosphere resulting in an enhanced zonal electric field.…”
Section: Discussionmentioning
confidence: 99%